Evaluation of the anti-inflammatory properties of a complex homeopathic product Modul8® using the BALB/c murine asthmatic animal model - Pretorius, Etheresia (University of Pretoria, 2013)
Thesis (PhD (Anatomy))--University of Pretoria, 2009.